Intracellular Ca(2+) signaling and store-operated Ca(2+) entry are required in Drosophila neurons for flight - Venkiteswaran, Gayatri (National Academy of Sciences, 2009)
Neuronal Ca(2+) signals can affect excitability and neural circuit formation. Ca(2+) signals are modified by Ca(2+) flux from intracellular stores as well as the extracellular milieu. However, the contribution of intracellular Ca(2+) stores and their release to neuronal processes is poorly understood. Here, we show by neuron-specific siRNA depletion that activity of the recently identified store-operated channel encoded by dOrai and the endoplasmic reticulum Ca(2+) store sensor encoded by dSTIM are necessary for normal flight and associated patterns of rhythmic firing of the flight motoneurons of Drosophila melanogaster. Also, dOrai overexpression in flightless mutants for the Drosophila inositol 1,4,5-trisphosphate receptor (InsP(3)R) can partially compensate for their loss of flight. Ca(2+) measurements show that Orai gain-of-function contributes to the quanta of Ca(2+)-release through mutant InsP(3)Rs and elevates store-operated Ca(2+) entry in Drosophila neurons. Our data show that replenishment of intracellular store Ca(2+) in neurons is required for Drosophila flight.